PARLIAMENTARY THRESHOLD IN CONSTITUTIONAL ELECTION IN 2019 (PHILOSOPHICAL REVIEW OF THE PRINCIPLES OF PEOPLE SOVEREIGNTY) - Muhammad Aziz Maftuh (JIL : Journal of Indonesian Law, 2020)
The 2019 Election leaves a problem with the people sovereignty in Indonesia, especially in the concept of the parliamentary threshold which is enforced at 4%. There are millions of legitimate votes that were wasted and did not convert into parliament because the party did not pass the threshold. The focus of this study is about the concept of parliamentary threshold in 2019 election which is reviewed from the people's sovereignty. This research is a library research (literature study) and employs a qualitative approach based on theoretical views and is reviewed from philosophical studies.  The data is collected tin the form of documentation from various books and scientific works related to this research. Based on the results, the concept of PT in the 2019 election resulted in the occurrence of wasted votes from valid votes so that millions of valid votes originating from the people's sovereignty were wasted. All new parties and small parties have very little chance of getting into parliament to voice the aspirations of their people. The disproportionality between the votes and the number of seats acquired becomes the reason that the concept of the parliamentary threshold in the 2019 elections is against the people's sovereignty.